Impairment of β-adrenergic regulation and exacerbation of pressure-induced heart failure in mice with mutations in phosphoregulatory sites in the cardiac CaV1.2 calcium channel - Hovey, Liam; Guo, Xiaoyun; Chen, Yi; Liu, Qinghang; Catterall, William A. (Frontiers in Physiology, 2023)
The cardiac calcium channel CaV1.2 conducts L-type calcium currents that initiate excitation- contraction coupling and serves as a crucial mediator of 𝛽-adrenergic regulation of the heart. We evaluated the inotropic response of mice with mutations in C-terminal phosphoregulatory sites under physiological levels of 𝛽-adrenergic stimulation in vivo, and we assessed the impact of combining mutations of C-terminal phosphoregulatory sites with chronic pressure-overload stress. Mice with Ser1700Ala (S1700A), Ser1700Ala/Thr1704Ala (STAA), and Ser1928Ala (S1928A) mutations had impaired baseline regulation of ventricular contractility and exhibited decreased inotropic response to low doses of 𝛽-adrenergic agonist. In contrast, treatment with supramaximal doses of agonist revealed substantial inotropic reserve that compensated for these deficits. Hypertrophy and heart failure in response to transverse aortic constriction (TAC) were exacerbated in S1700A, STAA, and S1928A mice whose 𝛽-adrenergic regulation of CaV1.2 channels was blunted. These findings further elucidate the role of phosphorylation of CaV1.2 at regulatory sites in the C-terminal domain for maintaining normal cardiac homeostasis, responding to physiological levels of 𝛽-adrenergic stimulation, and adapting to pressure-overload stress, and they challenge previous conclusions that these C-terminal phosphorylation sites are not important for regulation of CaV1.2 in the fight-or-flight response.